Optimizing Dayah Business Units in Aceh: An ANP Study - Siti Najma; Asmuni Asmuni; Saparuddin Siregar (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
This study investigates the key factors influencing the success of business units within Dayah (Islamic boarding schools) in Aceh Province, Indonesia. Employing the Analytical Network Process (ANP), the research gathers expert opinions and insights from academics, government officials, and practitioners. The analysis reveals that both internal and external factors significantly impact the management of Dayah business units. Internal factors identified as crucial for success include public relations resources, leadership capabilities, business management practices, natural resource availability, and adequate business capital. Externally, technological advancements, demographic shifts, political/governmental support, socio-cultural influences, and economic conditions all play a role in determining success. This research highlights the importance for stakeholders to consider these diverse factors when optimizing Dayah business unit management. It further offers practical recommendations for managing such units within the context of Aceh, Indonesia.==============================================================================================================ABSTRAK – Optimalisasi Unit Bisnis Dayah di Aceh: Studi ANP. Penelitian ini bertujuan untuk menganalisis faktor yang menjadi penentu kesuksesan dalam mengelola unit bisnis Dayah atau Pondok Pesantren yang ada di Provinsi Aceh, Indonesia. Penelitian ini menggunakan Analytical Network Process (ANP) untuk mengumpulkan opini dan pendapat dari akademisi, pejabat pemerintah dan praktisi. Analisis ANP menemukan bahwa kesuksesan dalam pengelolaan unit bisnis dayah di Aceh ditentukan oleh faktor internal dan faktor eksternal. Faktor internal yang teridentifikasi menjadi penentu keberhasilan adalah SDM, kepemimpinan yang kapabel, praktik manajemen bisnis, ketersediaan sumber daya alam, dan kecukupan modal usaha. Sementara dasi sisi eksternal, faktor penentu kesuksesan adalah kemajuan teknologi, perubahan demografi, dukungan politik/pemerintah, pengaruh sosial budaya, dan kondisi ekonomi. Hasil ini berimplikasi bagi para pemangku kepentingan dalam optimalisasi pengelolaan unit bisnis pada dayah-dayah di Aceh untuk memperhatikan faktor-faktor kesuksesan tersebut. Penelitian ini juga memberikan rekomendasi praktis yang bisa dijadikan acuan dalam pengelolaan unit bisnis yang dikelola oleh Dayah/Pondok Pesantren di Aceh, Indonesia.